2018
DOI: 10.1002/ptr.6086
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and clinical antihypertensive activity of Matricaria chamomilla extracts and their angiotensin‐converting enzyme inhibitory activity

Abstract: Three different extracts of Matricaria chamomilla L. were evaluated for their antihypertensive activity, these extracts were total alcohol extract (Extract 1), oil extracted (Extract 2), and water lifted after oil extraction (Extract 3). Quantitative and Qualitative analyses were carried out for all extracts. The 3 extracts were proved to be safe for human use. A single oral administration of the plant extracts (200 mg/kg) decreases both systolic and diastolic blood pressure of normotensive rats after 1, 1.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
1
19
0
4
Order By: Relevance
“…Os artigos apresentados nos resultados tratavam-se de ensaios clínicos realizados em diferentes regiões do mundo. Os estudos compartilham em seus desfechos a redução das pressões sanguíneas sistêmicas dos pacientes com hipertensão, crise hipertensiva e insuficiência cardíaca após a administração do captopril (ARNOLD et al, 2013;AWAAD et al, 2018;AZEVEDO et al, 2017;SALKIC et al, 2015;SUSALIT et al, 2011;YILMAZ et al, 2011), assim como a Pressão Arterial Diastólica (PAD) (AZEVEDO et al, 2017;SALKIC et al, 2015;SUSALIT et al, 2011). A PAS diminuiu de maneira semelhante, ficando entre os intervalos 11 e 13,7 mm Hg (ARNOLD et al, 2013;SUSALIT et al, 2011).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os artigos apresentados nos resultados tratavam-se de ensaios clínicos realizados em diferentes regiões do mundo. Os estudos compartilham em seus desfechos a redução das pressões sanguíneas sistêmicas dos pacientes com hipertensão, crise hipertensiva e insuficiência cardíaca após a administração do captopril (ARNOLD et al, 2013;AWAAD et al, 2018;AZEVEDO et al, 2017;SALKIC et al, 2015;SUSALIT et al, 2011;YILMAZ et al, 2011), assim como a Pressão Arterial Diastólica (PAD) (AZEVEDO et al, 2017;SALKIC et al, 2015;SUSALIT et al, 2011). A PAS diminuiu de maneira semelhante, ficando entre os intervalos 11 e 13,7 mm Hg (ARNOLD et al, 2013;SUSALIT et al, 2011).…”
Section: Discussionunclassified
“…Estados Unidos(ARNOLD et al, 2013), Bósnia e Herzegovina(SALKIC et al, 2015),Canadá (AZEVEDO et al, 2017) e Arábia Saudita(AWAAD et al, 2018). Quatro (66,7%) dos estudos da amostra final eram ensaios clínicos, sendo dois (33,3%) deles randomizados.…”
unclassified
See 1 more Smart Citation
“…In this study, we aimed to evaluate the antibacterial effect of three concentrations (50, 100 and 150) mg/ml of cold-water and boiling-water extracts of M. chmomilla flowers to inhibit growth of pathogenic bacteria isolated from urine of pregnant women with UTI, the results showed that 150mg Table 3, and there was non-significant differences (P-value>0.05) in antibacterial effect between imipenem 10 µg (positive control) and 150 mg/ml of hot-water extracts (Table 4). Matricaria chamomilla is an important medicinal plant was used in treatment of many infections such as respiratory tract infections and gastrointestinal tract infections in many countries [34]. Matricaria chamomilla flowers was used as antipyretic and carminative, in addition, flowers oil has been used in colic, flatulence and rheumatism [35].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in BP, following the administration of the extract, may be due to the amelioration of lipid homeostasis and/or the ability of the extract to relieve hyperglycaemia in diabetic animals. In a previous study, the effect of M. chamomilla L. on blood pressure was evaluated in rats [24]. The total alcohol extract from the aerial parts of the plant showed blood pressure lowering effects in hypertensive rats, with ACE inhibitory activity as a mechanism of action.…”
Section: Effect On Stz-induced Oxidative Stress Markers In Cardiac Timentioning
confidence: 99%